In vivo and in vitro activities and ADME-Tox profile of a quinolizidine-modified 4-aminoquinoline: A potent Anti-P. falciparum and anti-P. vivax blood-stage antimalarial - Basilico, N; Parapini, S; Sparatore, A; Romeo, S; Misiano, P; Vivas, L; Yardley, V; Croft, S; Habluetzel, A; Lucantoni, L; Renia, L; Russell, B; et al. (MDPI, 2017)
Natural products are a prolific source for the identification of new biologically active compounds. In the present work, we studied the in vitro and in vivo antimalarial efficacy and ADME-Tox profile of a molecular hybrid (AM1) between 4-aminoquinoline and a quinolizidine moiety derived from lupinine (Lupinus luteus). The aim was to find a compound endowed with the target product profile-1 (TCP-1: molecules that clear asexual blood-stage parasitaemia), proposed by the Medicine for Malaria Venture to accomplish the goal of malaria elimination/eradication. AM1 displayed a very attractive profile in terms of both in vitro and in vivo activity. By using standard in vitro antimalarial assays, AM1 showed low nanomolar inhibitory activity against chloroquine-sensitive and resistant P. falciparum strains (range IC50 16-53 nM), matched with a high potency against P. vivax field isolates (Mean IC50 29 nM). Low toxicity and additivity with artemisinin derivatives were also demonstrated in vitro. High in vivo oral efficacy was observed in both P.berghei and P. yoelii mouse models with IC50 values comparable or better than those of chloroquine. The metabolic stability in different species and the pharmacokinetic profile in the mouse model makes AM1 a compound worth further investigation as a potential novel schizonticidal agent.